2004
DOI: 10.1007/bf03166577
|View full text |Cite
|
Sign up to set email alerts
|

Low-field NMR water proton longitudinal relaxation in ultrahighly diluted aqueous solutions of silica-lactose prepared in glass material for pharmaceutical use

Abstract: Low-field (0.02--4 MHz) proton nuclear magnetic resonance (NMR) longitudinal relaxometry was applied to ultrahighly diluted aqueous solutions in order to detect physical modifications induced in the solvent by the dilution process. A mixture of silica-lactose (1.67.10 -5 M silica, 2.92-10 -2 M lactose) was initially solubilized in water or in saline, then submitted to eighteen iterative centesimal dilutions in water or in saline under vigorous vortex agitation and rigorously controlled atmospheric conditions, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
1
1

Year Published

2005
2005
2015
2015

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(34 citation statements)
references
References 22 publications
1
30
1
1
Order By: Relevance
“…9 Recent nuclear magnetic resonance studies of homeopathic solutions have shown that no long-lived alterations are present in the hydrogen bonding pattern of the bulk water 10,11 and that silicates leaching from the glass vials used to make the preparations may be responsible for some differences observed in relaxation times between different solutions. 12,13 The water cluster theory of homeopathy runs into additional trouble in light of the fact that many homeopathic preparations are soaked onto sugar pills, which are then dried to remove the solvent.…”
Section: It's In the Watermentioning
confidence: 99%
“…9 Recent nuclear magnetic resonance studies of homeopathic solutions have shown that no long-lived alterations are present in the hydrogen bonding pattern of the bulk water 10,11 and that silicates leaching from the glass vials used to make the preparations may be responsible for some differences observed in relaxation times between different solutions. 12,13 The water cluster theory of homeopathy runs into additional trouble in light of the fact that many homeopathic preparations are soaked onto sugar pills, which are then dried to remove the solvent.…”
Section: It's In the Watermentioning
confidence: 99%
“…53 Thus, the authors recommend the use of succussed controls, stored for the same time period and in the same type of container as their remedy counterparts. Using either nuclear magnetic resonance 54 or a biologic effect in mice, 55 a few reports documenting differences to this effect have been released. However, further attempts to demonstrate or replicate these differences 56 remained unsuccessful.…”
Section: Discussionmentioning
confidence: 99%
“…A series of studies using nuclear magnetic resonance imaging were able to document differences. 64,65 However, very thorough predecessor studies, conducted in a triple-blinded setup, were unable to confirm clear-cut and replicable differences, 66 and other independent studies yielded sometimes positive, 67 sometimes negative results. 68 A recent study using thermoluminescence found significant differences between a homeopathic test substance and succussed controls, 69 a result that awaits replication.…”
Section: Basic Researchmentioning
confidence: 99%